IJEM 2021
DOI: 10.31534/engmod.2021.2.ri.03d
|View full text |Cite
|
Sign up to set email alerts
|

Research on Rectal Tumor Identification Method by Convolutional Neural Network Based on Multi-Feature Fusion

Abstract: Aiming at the obscure features of tumors in rectal CT images and their complexity, this paper proposes a multi-feature fusion-based convolutional neural network rectal tumor recognition method and uses it to model rectal tumors for classification experiments. This method extracts the convolutional features from rectal CT images using Alexnet, VGG16, ResNet, and DenseNet, respectively. At the same time, local features such as histogram of oriented gradient, local binary pattern, and HU moment invariants are ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Among traditional image enhancement methods, the LBP method was also used. In the study, only the accuracy rate was considered in the hybrid method developed by the researchers, and the highest accuracy rate obtained as a result of the study was reported as 93.1% [6]. In the [7] study, researchers conducted a very remarkable study on the detection of polyps, which have a vital place in colorectal cancer.…”
Section: Related Studiesmentioning
confidence: 99%
“…Among traditional image enhancement methods, the LBP method was also used. In the study, only the accuracy rate was considered in the hybrid method developed by the researchers, and the highest accuracy rate obtained as a result of the study was reported as 93.1% [6]. In the [7] study, researchers conducted a very remarkable study on the detection of polyps, which have a vital place in colorectal cancer.…”
Section: Related Studiesmentioning
confidence: 99%